The Size of Costa Rica in the Non-Geographic World of Globalization - Sibaja Núnez, Enrique (2008)
What is something small? Small is an adjective, which refers to a relative condition; if we qualify something as small, we must necessarily do it in front of a reference point in relation to what is considered such. Thus, there is nothing that can be small by itself.